Diskursus Karya Seni, Kreator, Dan Kapitalisme - Purwasito, Andrik; Kartinawati, Erwin (Universitas Veteran Bangun Nusantara Sukoharjo, 2022)
This paper departs from the fact that capitalism has reached the stage of complete domination and hegemony. Art products, the art market, and creators are strongly influenced by the ups and downs of the market, the atmosphere and monetary stability, and market players such as auction houses, curators, collectors, collectors, art dealers, patronage, and the mass media. In such a position, it raises the question of how the position of the creator and his work in dealing with enthusiasts and observers of art, markets, and capitalism. Do the creators voluntarily submit and obey the choice to join the capitalist game, or do the creators have a strong bargaining position to maintain idealism and enthusiasm not to get caught up in the game of capital and political games. It is a document study, this article to answer the above questions. As a result, there are two perspectives: first, the perspective of artwork as a commodity that occurs in the current era, and the second is the artwork as an aesthetic object. In the perspective of art as a commodity, creators generally follow market tastes, assisted by patronage, collectors or collectors, and other elements such as curators and mass media. This capitalism employs a strategy called “frying fry.” The second perspective is the artwork as prestige and increasing social status. In this era, creators still have a good bargaining position because there are no market access constraints.